Developing Project-Based E-Modules for Correspondence Subject - Handayani, Wuni; Wulandari, Siti Sri (Universitas Negeri Surabaya, 2023)
This study aims to develop and analyze the feasibility of project-based e-modules for correspondence subjects. This study used an adapted Research and Development (R&D) model consisting of Define, Design, Development, excluding the dissemination stage. The findings of this study showed strong validation scores from material experts (86.81%), language experts (90.55%), and graphics experts (81.11%) categorized as